1991
DOI: 10.1159/000470446
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Echocardiographie Assessment of the Severity of Acute Pulmonary Embolism

Abstract: The assessment of the severity of acute pulmonary embolism (PE) by imaging and Doppler echocardiography is prospectively studied in 48 patients (mean age 58.5 years). The examination includes the échographie measurements of the right and left end-diastolic ventricular diameters and the continuous wave (CW) Doppler estimation of the pulmonary artery systolic pressure using the peak velocity of the tricuspid regurgitation flow. The results are compared with the hemodynamic data obtained through catheterization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…6 reported on good agreement between systolic pulmonary arterial pressure and its Doppler estimate based on continuous wave Doppler measurement of the tricuspid jet velocity (r=0.91) which was possible in 52 of 56 patients with pulmonary embolism. It is interesting that the correlation coefficient between Miller's index of pulmonary vascular obstruction and tricuspid jet velocity was lower than that between Miller's index and the ratio of diameters of right to left ventricle as measured with echocardiography (r = 0.43 and 0.68, respectively).…”
Section: Doppler Findings In Acute Pulmonary Embolismmentioning
confidence: 95%
“…6 reported on good agreement between systolic pulmonary arterial pressure and its Doppler estimate based on continuous wave Doppler measurement of the tricuspid jet velocity (r=0.91) which was possible in 52 of 56 patients with pulmonary embolism. It is interesting that the correlation coefficient between Miller's index of pulmonary vascular obstruction and tricuspid jet velocity was lower than that between Miller's index and the ratio of diameters of right to left ventricle as measured with echocardiography (r = 0.43 and 0.68, respectively).…”
Section: Doppler Findings In Acute Pulmonary Embolismmentioning
confidence: 95%
“…The Doppler sPAP assessment seems to be very reli able however; the correlation between sPAP obtained through catheterization and those calculated by Doppler is very good in several studies [7,16] and confirmed in acute PE [4]. The clinical evaluation of the RAP, which seems to be a potential limitation of the present analysis, has been validated in a previous study [17],…”
Section: Protocolmentioning
confidence: 67%
“…It is usually estimated from the cardiac output and the mean (m) PAP obtained through catheter ization [ 12] and by study of the pulmonary or total artery resistances [8,13], Our study used the Doppler sPAP cal culation from the TR flow, nearly constantly present in PE [4] and easy to record with CW Doppler. On the other hand, the recording of the pulmonary regurgitation…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations